Faktor yang Berhubungan dengan Upaya Pencegahan Penyalahgunaan Narkoba Pada Remaja Selama Pandemi di Kelurahan Kembangan Utara Tahun 2022 - Intan Muzdhalifa Maulana; Chahya Kharin Herbawani (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
During the pandemic, drug misuse in adolescents has many cases in the Jakarta area. BNN data shows Jakarta is in second place in 2020 with a total of 5,885 drug cases, and in 2021, as many as 4,749 patients. Information from the Kembangan Police that every month they have two drug cases, and the Kembangan Police have conducted counseling, but teenagers still fall into drug use. This study aims to determine the factors related to efforts to prevent drug misuse in adolescents in North Kembangan Sub-district in 2022. This study is cross-sectional with an accidental sampling technique on 310 adolescents in North Kembangan Village. The results of the bivariate analysis showed that there was a relationship between efforts to prevent drug misuse and gender (POR=0.427; 95% CI=0.427-0.705), education level (POR=47.131; 95% CI=14.015-158.494), knowledge (POR=0.067; 95% CI=0.022-204), attitude (POR=7.233; 4.196-12.469), family support (POR=9.960; 95% CI=5.551-17.871), and community environment (POR=1.765; 95% CI=1.065 -2,927). Multivariate analysis revealed that the level of adolescent education (POR=11.757; 95% CI=3.179-43.478) was the dominant factor. The government, institutes, schools, and the local area are expected to continue to carry out educational activities related to the threats of drugs. This is to seek promotive and preventive behavior for adolescents to avoid drug abuse.